Methodical aspects of arterial hypertension epidemiology monitoring in Russian Federation population: Target Federal Program «Arterial hypertension prevention and treatment in Russian Federation, 2002-2008» - V. V. Konstantinov; S. A. Shalnova; A. D. Deev; T. N. Timofeeva; A. V. Kapustina; Yu. A. Balanova; V. M. Ivanov; I. N. Lel'chuk; G. A. Muromtseva (Кардиоваскулярная терапия и профилактика, 2007)
The article is devoted to methodical recommendations on sample selection in regions with varying population size; representativeness assessment criteria; standard diagnostic methods for arterial hypertension (AH), risk factors, target organ status, and concomitant pathology; total cardiovascular risk assessment, as a part of the Target Federal Program «Arterial hypertension prevention and treatment in Russian Federation, 2002-2008».